2020
DOI: 10.21608/edj.2020.41503.1240
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Apoptotic changes induced by 5-Fluorouracil on the Lingual Mucosa and Salivary glands of male albino rats (Histological, Histomorphometric and Immunohistochemical Study)

Abstract: Chemotherapy tends to stop the growth and eliminate cancer cells even at distant sites. Most of them lead to adverse side effects and induce changes in normal tissues. The aim of the present study was to evaluate of apoptotic changes induced by 5-fluorouracil on the lingual mucosa and salivary glands of male albino rats through clinical, histological, immunohistochemical and histomorphometric assessments. Twenty male albino rats were divided equally into two groups. Control group did not receive any type of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…In the current study, observed Wistar rats' tongues showed a morphologic structure similar to other rat lines (Elmansy & Hegazy, 2020; Kullaa‐Mikkonen et al, 1987; Picoli et al, 2006; Verli et al, 2008) as the WWCPS rat (Goździewska‐Harłajczuk et al, 2018) or the Sprague–Dawley rat (Costa et al, 2013; Reginato et al, 2014).…”
Section: Discussionsupporting
confidence: 69%
“…In the current study, observed Wistar rats' tongues showed a morphologic structure similar to other rat lines (Elmansy & Hegazy, 2020; Kullaa‐Mikkonen et al, 1987; Picoli et al, 2006; Verli et al, 2008) as the WWCPS rat (Goździewska‐Harłajczuk et al, 2018) or the Sprague–Dawley rat (Costa et al, 2013; Reginato et al, 2014).…”
Section: Discussionsupporting
confidence: 69%
“…5-FU causes this state of imbalance. The majority of the chemotherapeutic agents also pose many challenges to the integrity of the salivary glands [4].…”
Section: Discussionmentioning
confidence: 99%
“…Regrettably, they have several harmful effects on both normal and malignant cells, which are injured through a variety of pathways associated with the stomatognathic system's key structures and functional activities [2,3]. One of these chemotherapeutic medicines is fluorouracil (5-FU), which is used to treat solid malignancies such as breast, GIT, ovarian, Pharmaceuticals 2022, 15, 232 2 of 14 and brain tumours [4]. 5-FU is a pyrimidine analogue that blocks the incorporation of thymidylate synthase into RNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be also be related to the fact that chemotherapeutic drugs can induce reactive oxygen species production leading to increased lipid peroxidation and calcium ions influx which also mediates apoptosis [9]. The epithelial atrophy in the acinar and ductal cells detected in group 2 of our study, obviously observed in the ED lining cells, could also be related to the impaired capacity of cell renewal due to the inhibitory effect of 5-FU on DNA replication and cell mitosis [27].…”
Section: Discussionmentioning
confidence: 64%